[BP.06.07] EFFECTS OF RENAL DENERVATION ON CARDIAC OXIDATIVE STRESS AND SYMPATHETIC NERVE REMODELING AFTER MYOCARDIAL INFARCTION IN CANINE. (September 2017) - Xu, M.; Lu, C.; Song, L.
Abstract : Objective: To observe the effects of RDN on the cardiac Oxidative Stress and ventricular remodeling due to MI in canine. Design and method: Anterior myocardial infarction was produced by gelatin sponge embolization of the left anterior descending artery. Eighteen canine were randomly divided into three groups. SHAM group (Sham operation group, renal arteriography performed a week after coronary angiograph, n = 6), MI group (renal arteriography performed a week after MI, n = 6), RDN group (RDN performed a week after MI, n = 6). Four weeks post-MI, echocardiography examination was administered to identify left ventricular end-diastolic dimension (LVEDD), left ventricular end-systolic dimension (LVESD), fraction shortening (FS) and left ventricular ejection fraction (LVEF). Left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP) and heart rate (HR) were measured. Myocardial superoxide dismutase (SOD) activity, malondialdehyde (MDA), superoxide anion (O2) and expression of p47phox mRNA were detected. Immunohistochemical assay was used to analyze the distribution and density of tyrosine hydroxylase (TH) positive staining nerve fibers in kidney. Serum creatinine was detected 4 weeks post-MI to assess renal function. Results: Compared with SHAM group, LVEF, FS and LVSP were decreased in MI group and RDN (P < 0.05), but LVEDD, LVESD and LVEDP were increased (P < 0.05). In contract, compared with MI group, LVEF was increased (P = 0.028), while LVEDD and LVESD were significantly lowered in RDN group (P < 0.05), but no significant differences were observed in FS and LVSP between the two groups (P = 0.092/0.931). There were no significant differences in heart rate among the three groups (P = 0.621). Although SOD lower and the O2-, MDA and p47phox mRNA were higher in MI group and RDN group, compared to the MI group(P < 0.05). Between-group comparisions demonstrated no differences in serum creatinine (P = 0.706). Conclusions: RDN should have effects to decrease the level of cardiac oxidative stress, attenuate cardiac remodeling, and improve heart function, without affecting renal function in post-MI HF canine model.